Characterization of the unique biomechanical behavior of right ventricle using experimental and constitutive modeling approaches - Liu, Wenqiang, author; Wang, Zhijie, advisor; Puttlitz, Christian, committee member; Bark, David, committee member; Chicco, Adam, committee member (Colorado State University. Libraries, 2022)
Ventricle dysfunction leads to high morbidity and mortality in heart failure patients. It is known that right and left ventricles (RV&LV) are distinct in their embryologic origins, anatomies and functions, as well as the pathophysiology of ventricular failure. However, how exactly the RV is distinct from the LV in their biomechanical properties remains incompletely understood. Furthermore, the prevalence of RV failure is significantly increased in the later stages of diseases such as pulmonary hypertension (PH) and heart failure with preserved ejection fraction, and the clinical management and treatment of RV failure are persistently challenging. This calls for a further understanding of the mechanisms of RV failure including the biomechanical mechanism. In addition, ventricular tissues are viscoelastic, which means both energy storage (originated from elasticity) and energy loss (originated from viscosity) are present during the deformation. However, the investigation of ventricular tissue viscoelasticity is much less than that of the elasticity, and it is largely unknown how the RV viscoelastic behavior changes during RV failure progression and impacts on the physiological function of the chamber. To fill these knowledge gaps, the overall goal of my study was to investigate the unique biomechanical properties of the RV in its physiological and pathological functions using experimental and constitutive modeling approaches. The Specific Aims are: 1) Develop the experimental protocols and characterize ventricular tissue passive static and dynamic mechanical properties in both large and small animals; 2) Adapted and performed constitutive modeling of ventricular tissue static and dynamic mechanical behaviors; 3) Quantify the changes in RV biomechanics during the maladaptive remodeling induced by pulmonary hypertension. At the completion of my study, I established the ex vivo testing protocols and provided fundamental data regarding static and dynamic mechanical differences between the healthy left and right chambers to delineate the unique biomechanical properties of the RV. I also adapted the constitutive models to capture static and dynamic mechanical behaviors of the RV. Finally, I quantified the biomechanical changes of the RV during the RV failure development and offered new insights in the contributions of the RV tissue biomechanics to the organ function. The findings were obtained from both large and small animals' species, which are translational to human diseases and a strong addition to the current literature of RV failure. More importantly, the investigation on the viscoelastic (dynamic) mechanical properties of the RV and the changes of viscoelasticity in RV failure progression is highly novel. The constitutive modeling of the RV biaxial viscoelastic behavior is pioneering and unique in the computational study of the RV. In summary, this study will deepen the understanding of the biomechanical mechanisms of RV failure and assist with the development of new computational tools for diagnosis and treatment strategies.
Keywords: fully nonlinear viscoelastic; quasi-linear viscoelastic; structural-function relationship; large animal model; ex vivo mechanical tests; right ventricle